Exploring the Relationship Between Brand Awareness, Brand Trust, and Brand Credibility Towards Floraison Customer Loyalty Through Consumer Satisfaction as an Intervening Variable - Artasuma, Luh Devi; Suardana, Ida Bagus Raka (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Tejakula Lestari Jaya, the manufacturer of Floraison products, is located in Buleleng, Bali, where this study was conducted. The results show that brand awareness, brand trust, and brand credibility have a positive and significant impact on customer satisfaction and customer loyalty. Consumer satisfaction also acts as a significant mediator of brand awareness, brand trust, and brand credibility on customer loyalty. The purpose of this study was to determine how brand knowledge, brand trust, and brand credibility affect customer satisfaction, as well as customer loyalty to Floraison's skincare and body care products. With an average value of brand recognition indicators of 4.24 and company characteristics of 4.15, customers indicate that Floraison products are of high quality, which contributes to loyalty. Therefore, increasing brand awareness and brand trust is very important for companies to maintain.